Unlocking Self-Directed Learning Readiness: A Systematic Exploration of Influential Factors - Piratheeban, K.; Bandara, L.M.K. (University of Colombo, Sri Lanka, 2024)
Self-Directed Learning Readiness (SDLR) is critical in contemporary education, enabling learners to take ownership of their learning processes. This systematic literature review consolidates insights from 23 studies published between 1986 and 2023 to analyze factors influencing SDLR across diverse educational contexts. The objectives were to identify, categorize, and understand the factors affecting SDLR, providing a comprehensive framework to inform educational strategies and policies. The methodology involved a rigorous selection process using databases such as PubMed, Google Scholar, JSTOR, ERIC, and Science Direct. Inclusion criteria were established to ensure relevance and quality, focusing on studies specifically addressing SDLR and pertaining to educational settings. A standardized extraction form was used to capture study details, and thematic analysis was employed to identify recurring themes and variations. Biases were minimized through a systematic approach to literature selection and data extraction. The review identified 50 factors influencing SDLR, categorized into five primary themes: student-related, contextual, teacher-related, sociocultural, and technological factors. Student-related factors were further divided into personal attributes, psychological factors, cognitive factors, and behavioral factors. Contextual factors were grouped into environmental, interpersonal, and institutional subthemes. Teacher-related factors were categorized into instructional approaches and support and feedback. Sociocultural factors included cultural influences and academic landscape, while technological factors were divided into technology access and competencies, and integration and utilization. Key findings reveal that student traits like motivation and self-efficacy, contextual elements such as family support and learning environments, and teacher-related practices significantly shape readiness for self-directed learning. Sociocultural influences and technological advancements also play critical roles in enhancing SDLR by shaping learning approaches and providing supportive tools. This study provides a comprehensive framework to identify and categorize factors influencing SDLR, emphasizing the importance of understanding these dynamics to inform tailored educational strategies and policies. By addressing these factors, educators and policymakers can foster environments conducive to self-directed learning, equipping students with essential skills for lifelong learning and success in an increasingly complex world.
Keywords: Self-directed Learning Readiness; Factors affecting online learning; Student autonomy; Self-efficacy